Efficacy and safety of endoscopic resection techniques of large colorectal lesions: experience of a referral center in Italy. Issue 4 (19th July 2021) - Papparella, Luigi Giovanni; Barbaro, Federico; Pecere, Silvia; Gibiino, Giulia; Burrelli Scotti, Giorgia; Napoli, Marco; Boskoski, Ivo; Petruzziello, Lucio; Costamagna, Guido
Abstract : Background: Endoscopic mucosal resection and submucosal dissection (ESD) are treatments of choice for superficial neoplastic colorectal lesions. Only a few studies have compared these techniques. Aim: To compare the efficacy and safety of endoscopic piecemeal mucosal resection (EPMR), ESD and hybrid-endoscopic submucosal dissection (H-ESD) of large colorectal lesions in a Western endoscopic center. Methods: This is a retrospective analysis on a prospective medical database of consecutive colorectal superficial lesions larger than 20 mm, resected by EPMR, ESD or H-ESD collected from 2015 to 2019. Results: Two hundred twenty-nine colorectal lesions were included. All lesions were completely endoscopically resected, 65.9% by EPMR, 19.7% by ESD and 14.4% by H-ESD. Endoscopic control after the index procedure was available for 86.5% patients. Among these patients, 80% had a second follow-up colonoscopy. The overall recurrence rate was 13.2, 0 and 6.1% for EPMR, ESD and H-ESD respectively, with a significant difference between EPMR and ESD. All recurrences were endoscopically treated during follow-up procedures. Risk of complications was not significantly different between the three groups. Conclusions: EPMR, ESD and H-ESD are effective and safe procedures. Recurrence rate in EPMR was higher but can be managed endoscopically with high success rates. EPMR is faster and technically simpler so should be considered a potential first-line therapy for colorectal superficial neoplastic lesions.